Isolated cricoid fracture associated with blunt neck trauma. Issue 7 (20th June 2007) - Oh, Je Hyeok; Min, Hyun Seok; Park, Tae Ung; Lee, Sang Jin; Kim, Sung Eun
Abstract : A 32-year-old woman without a remarkable history presented at the emergency department with strangulation of the neck. CT scans of the neck revealed a displaced cricoid fracture. Six days after admission to hospital, hoarseness and dyspnoea disappeared. On the 10th day, the patient was discharged without complications. The traditional treatment guidelines for laryngeal trauma have recommended an early surgical intervention after immediate tracheotomy in cases of displaced fractures of the cricoid cartilage. The patient could be treated successfully through continuous monitoring of airway obstruction without surgical management.